A study on cost analysis of oral antihypertensive drugs available in India - AVANTHI E; Allen Joe Rodrigues; Abhishek Achar; Mahesh G K; Anand Koppal (Journal of Applied Pharmaceutical Research, 2022)
The major health care problem in developing world is shifting from communicable diseases to non-communicable disease which causes morbidities more than mortality affecting the personal efficiency. Hypertension is a major health care burden in developing countries like India causing both morbidity and mortality. Few studies shows that the hypertension prevalence has raised from 2% to 15% in rural population and 2% to 25% in urban population in last six decades in India. This research work aims to enumerate the price of commonly available oral antihypertensive drugs in India. It also aims to study the cost variation of oral antihypertensive drugs. The present study was carried out in the department of Pharmacology in a tertiary care medical college in south India. The cost analysis of individual drugs by different manufacturers were done. Percentage of cost variation was analysed. The variation in cost of most of the antihypertensive drugs is more than 100%. It’s found maximum in Amlodipine (5mg) with cost variation of 625%, Atenolol 100 mg with cost variation of 413%. In India there is a wide price variation among antihypertensive drugs. The major gap in the cost variation of antihypertensive drugs to be narrowed for the benefit of the patients. So the government and the prescribing doctors should think about the huge difference in cost and work in the direction of benefitting the patient.